Pengembangan Multimedia Interaktif Desain Komunikasi Visual di SMK Kartika XX-1 Makassar - Ina Meiliyanthi; Hasanah Nur; Anas Arfandi (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This study aims to develop interactive multimedia on vocational basic subjects that are valid, practical and effective for use in Middle and Vocational Schools. The method used in this study is Research and Development (R&D) using a 4-D development model with the stages of define, design, develop, and deploy. From a series of research stages, an Interactive Multimedia was produced in the Vocational Basic Subject of Visual Communication Design. Software testing is done by validity test, practicality test and effectiveness test. The results of reliability testing by expert validation and blackbox tests show that the application is valid to use. The practicality testing research subjects were 13 respondents from students at SMK Kartika XX-1 Makassar, from the test results obtained responses in the very practical category of using the application, for the overall test results, indicating that the application was valid, practical and effective and very feasible for use in actual situations and conditions.